Some Issues Concerning the Formation of The Common Economic Space Of Kazakhstan, Russia and Belarus - Kozłowski, Waldemar; Kerimova, Ukilyay; Yessengaziyeva, Saule; Rakhimzhanova, Gaukhar (Olsztyn Economic Journal, 2014)
The article discusses the issues of creating a common economic zone with the countries of the Common Economic Space by comparing this economic area to the area of the European Union. Analysis of contracts for its establishment is for consideration, as well as the pluses and minus of the implementation of the grant agreement on the CES industrial countries. A comparison of these two economic zones with similar economic problems will enable the future of their cooperation.